Field notes contributed by Velma A. Keerbs, Mallard, Iowa, winter 1983-1984 - Keerbs, Velma A.et al (1983)
Field notes were contributed by Velma A. Keerbs, Mallard, Iowa, winter 1983-1984. This was her first report and included a Bald Eagle in Palo Alto County, a Barred Owl near Emmetsburg, six Snow Buntings and a Rusty Blackbird. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1983-1984. Epson - sheet feed/flatbed